Obstetrics–Gynecology Educational Achievements in Iran (1979-2017): Trends, Consequences and Future Implications - Shima Tabatabai (Tehran University of Medical Sciences, 2021)
Background: To study the current trends in Obstetrics–Gynecology (Ob-Gyn) education and workforce in Iran since 1979 and to discuss the consequences and implications.